Analysis of Financial Management and Financing in the Development of Entrepreneurship and MSMEs - Muhammad Harpis; Yonatan Aggat Sagulu; Martupa Malau; Intan Siagian; Evinia Br Sebayang (Jurnal Pendidikan Vokasi Indonesia, 2026)
Regional economic development is one of the main priorities in improving the welfare of Indonesian society. One method considered effective in achieving this goal is the advancement of entrepreneurship and Micro, Small, and Medium Enterprises (MSMEs). Medan Selayang is one of the regions experiencing growth in the entrepreneurship and MSME sectors. This study aims to analyze financial management and financing patterns in supporting the development of entrepreneurship and Micro, Small, and Medium Enterprises (MSMEs) in Medan Selayang District. MSMEs play a strategic role in the regional economy; however, they still face various challenges, particularly in financial management and access to financing sources. This study employed a qualitative descriptive approach with data collection techniques conducted through interviews, observations, and documentation involving MSME actors in Medan Selayang. The results of the study indicate that most MSME actors still apply simple financial management practices, have not clearly separated business finances from personal finances, and lack proper financial report recording. In terms of financing, MSME actors rely more on personal capital and informal loans rather than formal financial institutions due to limited financial literacy, collateral constraints, and administrative procedures. This study emphasizes the importance of improving financial management literacy, business assistance, and expanding inclusive access to financing in order to encourage entrepreneurial growth and the sustainability of MSMEs in Medan Selayang. The findings of this study are expected to provide recommendations for policy development that supports entrepreneurship and MSMEs at the local level, particularly in Medan Selayang.